Fostering The Entrepreneurship for The Group of Housewives in Klambir Lima Kebun Village - Mesra B; Sri Wahyuni; Dewi Nurmasari Pane (Journal of International Conference Proceedings (JICP), 2021)
Community service aimed to help in solving problems faced by groups of housewives, namely by providing entrepreneurial training that they would use later in the business. The form of training was given in the form of training in strengthening the entrepreneurial spirit first and continued with entrepreneurship training by demonstrating the processing of local commodities, namely pumpkin into wajik, dodol, and chips. The service activities carried out on the group of housewives showed that housewives already had skills in producing products made from pumpkins. The products consisted of wajik, dodol, and chips. It was hoped that the presence of these products would increase their income in the welfare of the family. Thanks to the Ministry of Research, Technology and Higher Education of the Republic of Indonesia for providing financial support through the 2019 budget year service program, the University of Pembangunan Panca Budi, the Group of Housewives in Klambir Lima Kebun Village as well as those involved in this community service activity.